Family Resilience During Pandemic Based on the Existence of Pregnant Women and Family Income in Madiun, Indonesia - Qurniyawati, Eny; Sebtalesy, Cintika Yorinda; Andriani, Linda; Ssekalembe, Geofrey; Nasr, Nayla Mohamed Gomaa; Razzan, Fadhil Muhammad (Al-Sihah : The Public Health Science Journal, 2023)
During the COVID-19 pandemic, pregnant women were reported to face a disproportionately high death rate, reaching nearly 25% of the global pregnant population. According to data from POGI (Indonesian Association of Obstetrics and Gynecology) as of April 2021, 536 pregnant women in Indonesia were exposed to COVID-19 resulting in 16 deaths. This implies an estimated mortality rate of 32 per 1000. Family with pregnant women experience more worries about the COVID-19 infection, which reduces resilience capacity. Therefore, this study aimed to examine the impact of certain factors including husband education, profession, family size, and wealth, as well as the presence of pregnant women on the resilience of family in facing the COVID-19 pandemic. A cross-sectional design and analytical observational method were used, while the samples comprised 100 households selected using g-form and accidental sampling. In addition, the data collected were analyzed with the chi-square test. The results showed that family income OR = 2.46 (95% CI = 1.08 - 5.61; p-value = 0.03) and the presence of pregnant women OR = 5.40 (95% CI = 2.25 - 12.96; p-value 0.01) had a significant relationship with family resilience. Specifically, low family resilience was related to lower income and the presence of pregnant women in the household.